Genetic structure and diversity of populations of polyploid Tibouchina pulchra Cogn. (Melastomataceae) under different environmental conditions in extremes of an elevational gradient - Brito, Vinï¿½cius L. G.; Mori, Gustavo M. [UNESP]; Vigna, Bianca B. Z.; Azevedo-Silva, Marianne; Souza, Anete P.; Sazima, Marlies (Springer Nature, 2016)
The genetic structure and diversity of plants may change significantly in an elevational gradient because different elevations regulate different ecological conditions. Several factors may influence genetic variation, such as mutations, selection, genetic drift, and gene flow. The aim of the present study was to evaluate the genetic structure and diversity of populations of Tibouchina pulchra Cogn. (Melastomataceae) trees in two extremes of an elevational gradient experiencing different environmental conditions. Nine polymorphic microsatellite loci were used to measure the genetic diversity of 14 adult populations, whose structure was evaluated using frequentist and Bayesian analyses. We also carried out progeny structure and paternity analyses comparing the number of fathers of each progeny and the probability of the progeny genotypes to be the result of selfing in order to evaluate the possible current processes leading to such genetic structure. Genetic structure analyses indicated the existence of genetic differentiation between populations in adults and progenies, but with a contact interface between them. The population from the higher region showed smaller genetic diversity when compared to the population at the lower region. However, the pollen variability delivered to the stigmas at the higher region was not different from that of the lower region. These results may be explained by the dynamics of gene flow mediated by pollen, especially by the different amounts of pollination events in each region, as well as local adaptation, distribution, and reproduction characteristics of T. pulchra.
Keywords: Atlantic rainforest; Manacï¿½-da-Serra; Pollen flow; Polyploidy; Serra do Mar